The Effect of Warm Compresses on Dysmenorhore In Adolescents in The Selomartani District Kalasan Sleman - Wijayanti, Heny Noor; Verawati, B.; Is, Aan (Journal of Midwifery, 2024)
Many women experience menstrual problems, including pain during menstruation, known as dysmenorrhea. Dysmenorrhea pain is the most common complaint and is experienced by many women. Many teenagers experience dysmenorrhea in the first three years after menarche. Young adult women aged 17-24 years are the ones who most often report painful menstruation. This study aims to determine the effect of giving warm water compresses on dysmenorrhea in teenagers in Selomartani Village, Kalasan, Sleman. This research was carried out as a quasi-experiment so that data was taken before treatment and after treatment. Data was collected using a questionnaire, then analyzed with one group pre and post test. The research results showed that there was an effect of giving warm water compresses on dysmenorrhea in teenagers in Selomartani Village, Kalasan, Sleman, where the p value was <0.05.